Aktualisasi Peran Sosial Wanita Cina di Jabodetabek - Muas, R. Tuty Nur Mutia; Witanto, Eddy Prabowo (Makara Human Behavior Studies in Asia, 2005)
Actualization Of Chinese Women’s Social Role In Jabodetabek. This research is based on a primary question "Why the actualization of Chinese women's social role is not frequently seen in Indonesia?"; Does it happen because of their 'double minority' position? ; Do they have willingness to show their social role in society? ; And some other questions around the issue which are interesting to find the answer. The focus of this research relates to human behavior which is hard to measure, so this research uses qualitative research methodology which is based on symbolic interaction perspective. An analysis on 101 respondents' answers to the questionnaires, and the result of action research and deep interview with some people who have been chosen, give us some conclusions. One of them: as human beings, even though Chinese women in Jabodetabek are on double minority position, they still have the willingness to actualize their social role. The area that becomes their primary choice is in religion, but some of them choose other areas like arts, sports, even politics. Their primary obstacle for actualizing the role in social life is the process of exclusiveness that has happened and has been carried out in their daily lives whether they realize it or not. It happens on their four social living aspects: tradition, language, education, and social environment. The main factor that has motivated them is their self awareness as part of Indonesian society. However, the material interest also has a slight influence on them.